2013
DOI: 10.1021/ar400133k
|View full text |Cite
|
Sign up to set email alerts
|

Constructing Functional Mesostructured Materials from Colloidal Nanocrystal Building Blocks

Abstract: Through synthesizing colloidal nanocrystals (NCs) in the organic phase, chemists gain fine control over their composition, size, and shape. Strategies for arranging them into ordered superlattices have followed closely behind synthetic advances. Nonetheless, the same hydrophobic ligands that help their assembly also severely limit interactions between adjacent nanocrystals. As a result, examples of nanocrystal-based materials whose functionality derives from their mesoscale structure have lagged well behind ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
49
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 60 publications
0
49
0
Order By: Relevance
“…Such differences might play a role in the interaction with structure directing agents in the synthesis of mesoporous materials. 9 In addition, most amino acids contain only C, H, O and N, which burn off easily, and do not introduce new elements in, e.g., a nanocomposite of the high temperature NCs already suggested that Gln is directly bound to the NC surface. However, this is an indirect deduction and does not give any information about the fate of the original ligand, dodecanoic acid (DDAc).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Such differences might play a role in the interaction with structure directing agents in the synthesis of mesoporous materials. 9 In addition, most amino acids contain only C, H, O and N, which burn off easily, and do not introduce new elements in, e.g., a nanocomposite of the high temperature NCs already suggested that Gln is directly bound to the NC surface. However, this is an indirect deduction and does not give any information about the fate of the original ligand, dodecanoic acid (DDAc).…”
Section: Resultsmentioning
confidence: 99%
“…Examples include (i) capacitor 5 or superconducting 6,7 nanocomposite thin films formed using a methanol-based precursor solution containing both molecular precursors for the matrix and dispersed metal oxide NCs (ii) nanocrystal-in-glass composites, fabricated from aqueous dispersions of indium tin oxide 8 or (iii) mesoporous mate-rials, constructed from NC building blocks by electrostatic interaction with a structure directing block-copolymer. 9 De-aggregation of NCs in nonpolar solvents is often attained by providing a steric stabilizer. [10][11][12][13][14] In order to achieve colloidal stability in polar solvents, the hydrophobic, steric ligands need to be exchanged for organic or inorganic polar ligands.…”
Section: Introductionmentioning
confidence: 99%
“…[ 24,27,30,[58][59][60][61] In these early studies, CNFs already demonstrated remarkable stability during both chemical and electrochemical transformations. For example, CdSe CNFs undergo sequential cation exchange to Cu 2 Se, Ag 2 Se, and PbSe CNFs without signifi cant framework degradation or loss of order.…”
Section: Research Newsmentioning
confidence: 99%
“…To date, the most successful CNF assembly schemes have employed electrostatics as an interfacing strategy. [ 21,22,24,25,[27][28][29][30] Here, the surfaces of the nanocrystal components are ionic in character; both ligandcoated [ 31 ] and ligand-stripped nanocrystals [66][67][68] are suitable in this regard.…”
Section: Research News 2 Engineering the Surfaces Of Colloidal Nanocmentioning
confidence: 99%
See 1 more Smart Citation